The Effect of Short-Term Temperature Pretreatments on Sugars, Organic Acids, and Amino Acids Metabolism in Valencia Orange Fruit - Mingfei Zhang; Rangwei Xu; Guochao Sun; Yunjiang Cheng; Zhihui Wang (Journal of Food Quality)
Temperature pretreatment is one of the most important factors which significantly affects the postharvest quality of citrus fruit. In this study, late-ripening Valencia orange (citrus sinensis) fruits were used to investigate the effect of short-term treatment at low (6°C), room (20°C), and high (40°C) temperatures on fruit quality. Our results revealed that both low and room-temperature treatments maintained the content of sugars and organic acids, whereas high-temperature treatments elevated the accumulation of sugars but decreased the content of citric acid. In fruit peel (flavedo and albedo), the accumulation of sugars and organic acids responding to temperatures was diverse and mostly different from that in the pulp. Meanwhile, GABA and several amino acids were upregulated under short-term high-temperature treatment but downregulated in response to low-temperature treatment in both peel and pulp. Furthermore, PCA and correlation analysis revealed that the short-term temperature treatments changed the metabolic flow, and GABA was positively correlated with sugars and organic acids. Our study analyzed the metabolic changes of fruit peel and pulp in response to short-term temperature treatments and revealed that GABA may act as a signaling molecular involved in temperature-controlled quality changes.